Kimberley Capers: An Outback 'Whodunnit?' - Fullarton, Alexander; Pinto, Dale (The Tax Institute, 2020)
In November 2019, a sequel to the mass-marketed tax avoidance schemes of the 1990s appeared in the West Kimberley region of Western Australia. The Australian Broadcasting Commission ran a series of articles revealing how hundreds of disaffected and isolated taxpayers engaged in a tax scam potentially involving tens of millions of dollars. In itself the scam was short, sharp and almost trivial, compared to the billion dollar mass-marketed tax avoidance schemes which involved over 40 000 taxpayers nationwide and took years to evolve and settle. The ‘sideshow’ was over almost before it started, and nearly went unnoticed from a national perspective. However the ‘when, what, where and how’ are not the key elements of this paper – it is the ‘who and why’ that are investigated. This paper is an overview of what can go wrong when taxpayers feel disaffected and isolated from their government.